Perfil clínico e molecular de pacientes portadores de neoplasia endócrina múltipla tipo 1 - Pinheiro, Daniel Pascoalino (2012)
MEN-1 is a rare autosomal dominantly inherited syndrome caused by a mutation that inactivates the MEN1 gene (tumor suppressor gene). The clinical manifestation of MEN-1 is defined by the associated occurrence of at least two of the three main endocrine tumors related to MEN1: primary hyperparathyroidism (PHP), pituitary adenoma (PA) and gastroenteropancreatic tumors (GEPs). The MEN1 gene, involved in the syndrome, consists of 10 exons (exon 1 and 832 bases of exon 10 are not translated) encoding a protein that contains 610 amino acids called MENIN. Over 459 different germline mutations have been identified in families with MEN1. A total of eight families and two sporadic cases were studied, resulting in 33 patients with MEN1, with 31 familiar MEN1 and two sporadic MEN1. Four milliliters of peripheral blood were collected for DNA and RNA extraction using the QIAamp DNA Blood Mini and QIAamp RNA Blood Mini Kits from QIAGEN®. Each of the nine coding exons of the MEN1 gene was amplified by the Polymerase Chain Reaction (PCR). The PCR products were purified and standard protocols were used for cycle sequencing. Sequences were determined after capillary electrophoresis and analyzed using the software CondonCode Aligner®, in order to draw a mutational profile. RNA samples were converted into cDNA and analyzed in real time PCR. The average age of patients was 40.7 ± 12.7 years, and the prevalence of tumors associated with MEN1 was: PHP, 87.8% (29/33), pituitary adenoma, 81.8% (27/33); GEPs, 54.5% (18 / 33), other tumors associated with MEN1, 63.6% (21/33). As the first manifestation in these patients, the pituitary adenomas prevailed, occurring in 57.5% (19/33). After automated sequencing of the entire coding region of the MEN1 gene, germline mutations were found in seven MEN1 families and in one of the sporadic cases. Three different mutations were identified: two missense mutations, c.597 C>T (H199H) e c.830 C>G (P277R); and one splice-site mutation, c.654 +1 G>T (IVS3+1G→T). We could not find any association between genotype-phenotype in these MEN1 patients. Differences in the gene expression profile were observed. The MEN1 gene in the studied patients was down regulated, when compared to healthy individuals.